TINDAK PIDANA MENYALAHGUNAKAN NARKOTIKA GOL 1 BUKAN TANAMAN (Studi Kasus Pada Putusan No. 1163/PID.SUS/2020/ PN Jkt.Pst): The Criminal Offense Of Using Narcotics Category 1 Non-Plant Drugs (Court Judgment on Decision Number 1163/PID.SUS/2020/ PN Jkt.Pst) - Sezi Hanugrah Suherman; Anang Iskandar (Reformasi Hukum Trisakti, 2024)
Narcotics is substance or drug that can be useful and for the treatment of certain diseases. However, use that not suitable for treatment will cause harm to the community. Narcotics abusers should be sentenced to rehabilitation, but in fact in decision No. 1163/PID.SUS/2020/ PN Jkt.Pst the judge imposed prison sentence of 3 years. The problem of how the form of punishment for people who abuse narcotics category 1 non-plant according to case No. 1163/PID.SUS/2020/ PN Jkt.Pst, and how the judge's consideration in imposing sanctions on the defendant in Decision No. 1163/PID.SUS/2020/ PN Jkt.Pst. The type of research is Normative Juridical with the nature of analytical descriptive research, by secondary data literature study is carried out. Analyzed with qualitative and deductive logic conclusions. The results showed that the judge-imposed Article 127 paragraph 1 and 3 years imprisonment to the defendant was considered inappropriate, because the verdict the defendant was only proven to use narcotics for himself, which according to Law No. 35 of 2009 concerning narcotics, the judge is obliged to sentence rehabilitation the abuser. In determining whether misuser should be rehabilitated, there must be evidence proving that the misuser is victim.